Bimbingan (Calistung) Baca, Tulis, Berhitung Di SDN 225 Polewali Dusun Polewali Desa Bonto Sinala Kecamatan Sinjai Borong - Suriyati, Suriyati; Amalia, Riski; Jamaluddin, Jamaluddin; Judrah, Muh.; Nur, Taufiq (PENDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The aThe aim of community service is to provide study guidance for students who are not yet fluent in reading, writing and arithmetic. The method used is guidance students in reading, writing and arithmetic using tools in the form of markers and whiteboards which consist of the preparation and evaluation stages. From the results of the reading, writing and arithmetic tutoring program (calistung) within a period of one month, it can be seen that there are several students who have started to recognize the letters of the alphabet A-Z are aable to read words even though they are a little stuttering are able to write the letters of the alphabet A-Z even though it is still upside down or some letters are still missing and the student is able to write his name. in terms of numeracy skills, students are able to knom addition 1-10 and students are able to memorize multiplications 1-3. So it can be concluded that students are able to read, write and count (calistung) well so that the learning process can run effectivelyim of community service is to provide study guidance for students who are not yet fluent in reading, writing and arithmetic. The method used is guidance students in reading, writing and arithmetic using tools in the form of markers and whiteboards which consist of the preparation and evaluation stages. From the results of the reading, writing and arithmetic tutoring program (calistung) within a period of one month, it can be seen that there are several students who have started to recognize the letters of the alphabet A-Z are aable to read words even though they are a little stuttering are able to write the letters of the alphabet A-Z even though it is still upside down or some letters are still missing and the student is able to write his name. in terms of numeracy skills, students are able to knom addition 1-10 and students are able to memorize multiplications 1-3. So it can be concluded that students are able to read, write and count (calistung) well so that the learning process can run effectively